2018
DOI: 10.1001/jamanetworkopen.2018.5909
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early Physical Therapy With Long-term Opioid Use Among Opioid-Naive Patients With Musculoskeletal Pain

Abstract: Key Points Question Is early physical therapy associated with long-term opioid use by patients with musculoskeletal pain? Findings In this cross-sectional analysis of 88 985 patients with shoulder, neck, knee, or low back pain, early physical therapy was associated with an approximately 10% statistically significant reduction in subsequent opioid use. Meaning By serving as an alternative or adjunct to short-term opioid use for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 31 publications
2
52
0
3
Order By: Relevance
“…[12][13][14] In the primary care setting, early physical therapy (PT) appears to be associated with lower utilization of advanced imaging, lower rates of lumbar spinal injections and lumbar spinal surgery, and improved patient satisfaction. [15][16][17][18][19] In the ED, a primary contact physical therapy model has been shown to reduce wait times and improve patient flow, directing patients to early effective care, and freeing emergency physicians to focus on other emergent cases. [20][21][22][23][24] A primary contact model involves the Physical Therapist acting as primary provider and autonomous practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In the primary care setting, early physical therapy (PT) appears to be associated with lower utilization of advanced imaging, lower rates of lumbar spinal injections and lumbar spinal surgery, and improved patient satisfaction. [15][16][17][18][19] In the ED, a primary contact physical therapy model has been shown to reduce wait times and improve patient flow, directing patients to early effective care, and freeing emergency physicians to focus on other emergent cases. [20][21][22][23][24] A primary contact model involves the Physical Therapist acting as primary provider and autonomous practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that early physical therapy for neck pain may decrease total treatment costs and the use of prescription medicines, including opioids [45]. The authors of another study reported that early physical therapy may reduce both the frequency and level of opioid use for all of the musculoskeletal pain regions [46]. The conclusion to be drawn here is that early physical therapy or exercise therapy may be a good option to reduce the use of opioids and/or other analgesics when the pain level remains low.…”
Section: Discussionmentioning
confidence: 99%
“…28 A cross-sectional analysis of US health insurance claims data from 2007 to 2017 linked early physical therapy to an approximately 10% statistically significant reduction in oral morphine milligram equivalent (MME) use for LBP (p=0.046), shoulder pain (p=0.03), and knee pain (p=0.007) in adults with no previous opioid prescriptions. 29 Although generally considered beneficial, with studies supporting minimal to moderate improvement in CLBP, the effectiveness of physical rehabilitation has not been well supported by systematic reviews. For example, 2011 and 2018 reviews concluded that there was insufficient data to support these interventions due to the heterogeneity of patients and interventions.…”
Section: Pros and Cons Of Nonpharmacologic Therapiesmentioning
confidence: 99%